Webservice Learning Preparation Report Polytechnic Indonusa Surakarta - Edy Susena; Dwi Iskandar; Muhammad Hari Wahyudi (Institut Teknologi Bisnis AAS Indonesia, 2021)
Polytechnic Indonusa Surakarta is a private university that has various study programs available. Some of the study programs must report learning preparation reports every semester which must be submitted and validated directly by Deputy Director I as an academic field. At first these activities were carried out manually and not yet computerized so as to facilitate program studies in conducting consultations and Deputy Director I who had a busy schedule but had to validate manually. This system was created with the aim of making it easier for Polytechnic Indonusa Surakarta side in collecting file, conducting consultation, signing signatures, and making learning preparation reports. Data collection methods used include the method of literature study, observation, interviews and documentation. This system will use a MySQL database with the PHP programming language with the Laravel framework. The method used in making this web service is the waterfall method. The result of the webservice learning preparation report is that the webservice system can facilitate both study programs in submitting and conducting consultations and Deputy Director I in conducting validation, consulting, and preparing learning preparation reports. This system will store data from reports that are entered into the webservice database